PROMOÇÃO DE RESILIÊNCIA URBANA NO BRASIL: NÍVEIS, AGENTES E POPULAÇÃO - Sgarbi, Allyne; Ferreira, Karolyne; Abiko, Alex (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The United Nations has pursued resilience goals from the Sendai Framework 2015-2030 as a lesson learned in the implementation of the Hyogo Framework (2005-2015) for Action on disaster risk management as a major contribution to the development of sustainable cities. According to data published in the Sendai Framework, during the 10-year period of the construction campaign of resilient cities, more than 1.5 billion people were affected by disasters in various ways, with an economic loss of more than 1, 3 trillion, and recorded the displacement of more than 144 million people caused by disasters aggravated by climate change. In the period 1995-2014, Brazil lost 182 billion due to the occurrence of natural disasters. In order to avoid further losses, Brazilian institutions have drawn up plans for disaster risk reduction and sought measures to increase the urban resilience of the municipalities most affected in the occurrence of natural disasters. This paper aims to identify the institutions that work to adapt the capacity of Brazilian cities to face disasters in monitoring, prevention and training during an event and also to reflect on the role of the Brazilian population in the prevention of material damages and fatalities.